The Effectiveness of Acceptance and Commitment Therapy on Self-Awareness and Self-Affirmation in Patients with Thalassemia - Karimi Asrami, Maryam; Mazdarani, Shahzad (Mental Health and Lifestyle Journal, 2024)
The present study aimed to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) on self-awareness and self-affirmation in patients with thalassemia. This research employed a quasi-experimental design with a pretest-posttest format and a control group. The statistical population consisted of female thalassemia patients who attended Bu-Ali Hospital in the city of Sari. Based on purposive sampling and predefined inclusion and exclusion criteria, a total of 40 participants were selected—20 assigned to the experimental group and 20 to the control group. To collect the required data, the study utilized the standard Self-Awareness Questionnaire by Nestor and Davis (2002) and the standard Self-Affirmation Questionnaire by Rathus (2003). For data analysis, multivariate analysis of covariance (MANCOVA) was used. The results indicated that Acceptance and Commitment Therapy had a positive and statistically significant effect on both self-awareness and self-affirmation in thalassemia patients treated at Bu-Ali Hospital in Sari. Therefore, it can be concluded that ACT is effective in improving self-awareness and self-affirmation in patients with thalassemia.